KARAKTER MORFOLOGI DAN PERTUMBUHAN SUBSPECIES KAYU MERAH (Pterocarpus indicus Willd.) ASAL PULAU SERAM, MALUKU DAN PULAU FLORES, NUSA TENGGARA TIMUR DI PERSEMAIAN - Vivi Yuskianti; Arianda Poetri Shofia Rochman; Nisa Oktaviani Lingga; Budi S Daryono (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2019)
Kayu merah (Pterocarpus indicus Willd), a high quality and multiple purpose tree, has been categorized as endangered species. Only a few know that kayu merah has two subspecies (forma) that are differentiated based on the surface structure of the central seed case. This study aims to know the differences on morphological and growth characters of two populations/subspecies kayu merah i.e. Pulau Seram, Mollucas (smooth pods, forma indicus) and Pulau Flores, East Nusa Tenggara (prickly pods, forma echinatus). The genetic relationship ofthese two populations/subspecies was analyzed using PBSTAT program, while their growth parameter analyzed using SAS program. The study found differences on morphological and growth characters of kayu merah from Pulau Seram and Pulau Flores. Kayu merah from Pulau Seram has many smooth spots and little grooves on the surface of its stem and has tapered leaf tip shape, while kayu merah from Pulau Flores has many grooves and little smooth spots, and has splitting leaf tip form. The two populations/subspecies were clearly clustered into their own group. Kayu merah from Pulau Seram has better growth than that of Pulau Flores. The result of this research has expected can support conservation and further utilization of the species in Indonesia by providing information on preliminary identification of the origin of kayu merah i.e. Pulau Seram and Pulau Flores as well as early indication of indicus and echinatus subspecies differences in the nursery.